Influence of long-scale length radial electric field components on zonal flow-like structures in the TJ-II stellarator. (12th July 2016) - Losada, U; Alonso, A; van Milligen, B Ph; Hidalgo, C; Liu, B; Pedrosa, M A; Silva, C
Abstract: The influence of long-scale length radial electric fields on zonal flows-like structures has been studied in the TJ-II stellarator. This relation has been investigated in the edge plasma using two electrical rake probes. The results presented here show an empirical correlation between the properties of long-range correlations (LRCs) with zonal flow-like structures and the magnitude of radial (neoclassical, NC) electric fields in TJ-II neutral beam heated plasmas. These experimental findings show that the enhancement of the NC radial electric field E r increases the magnitude of LRCs, considered as a proxy of zonal flows, while the radial correlation length of the plasma potential fluctuations was found to decrease by about 40%. A strong relation between the magnitude of electric field structures with long and short radial scales was found. The calculated E r × B shearing rate corresponding to the short scale length structures of the radial electric field may be sufficient to regulate turbulence.